Performance analysis of a data-offloading approach based on software-defined networking for heterogeneous networks - Romero Avendaño, Sebastian; Sánchez Huertas, Jann Camilo; Puerto Leguizamón, Gustavo Adolfo (IET communications, 2020)
This study presents the performance evaluation of a data-offloading algorithm developed and implemented in the framework of a software-defined network (SDN). The algorithm senses the network congestion and takes into account the constraints imposed to the throughput and delay in order to command a data offloading operation from the current active interface to another one available in a given host. Both, emulation and experimental demonstration of the approach were implemented in the open network operating systems in which multimedia services were transported within the SDN environment and assessed in terms of the algorithm parameters configuration. The experimental demonstration confirms the feasibility of the proposed algorithm to offload the traffic of a given data stream to a less congested available interface or network.